Cognition and objective sleep quality in post-COVID-19 patients - Carnes-Vendrell, Anna; Piñol-Ripoll, Gerard; Targa, Adriano; Tahan, Nuria; Ariza, Mar; Cano, Neus; Segura, Barbara; Junque, Carme; Béjar, Javier; Barrue, Cristian; , Nautilus Project Collaborative Group; Garolera, Maite; et al. (Frontiers in Psychology, 2025)
In the current study, we aimed (i) to evaluate sleep quality via wrist actigraphy monitoring of nonhospitalized and hospitalized post-COVID-19 condition (PCC) participants; (ii) to correlate actigraphy measures with subjective measures of sleep quality, such as the Pittsburgh Sleep Quality Index (PSQI); and (iii) to investigate whether total sleep time or sleep efficiency could affect PCC cognitive performance. We included 49 individuals with PCC from the NAUTILUS Project (NCT05307549 and NCT05307575) who were monitored for 1 week via actigraphy and who were also assessed with a comprehensive neuropsychological battery and the PSQI. We found that there were significant differences between nonhospitalized PCCs and hospitalized PCCs in the number of awakenings. We also found a correlation between the total sleep time of both measures (actigraphy and PSQI), but we did not observe correlations between objective and subjective parameters of latency and sleep efficiency. Regarding cognition and actigraphy measures, there was a trend of statistical significance in the performance of immediate visual memory, attention span and social cognition according to sleep efficiency. In conclusion, results indicate that although the PSQI provides clinically relevant indicators of sleep, there are divergent results between self-reported and objective sleep measures (actigraphy). Furthermore, we found a tendency toward statistical significance in cognitive performance in PCC participants according to their sleep efficiency which could indicate that is more important for cognitive function of post-COVID-19 patients than total sleep time.